2014
DOI: 10.1016/j.celrep.2014.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Effects of Tumor-Derived Complement

Abstract: SUMMARY We describe a role for the complement system in enhancing cancer growth. Cancer cells secrete complement proteins that stimulate tumor growth upon activation. Complement promotes tumor growth via a direct autocrine effect that is partially independent of tumor-infiltrating cytotoxic T cells. Activated C5aR and C3aR signal through the PI3K/AKT pathway in cancer cells, and silencing the PI3K or AKT gene in cancer cells eliminates the progrowth effects of C5aR and C3aR stimulation. In patients with ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
174
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(191 citation statements)
references
References 25 publications
3
174
3
1
Order By: Relevance
“…Thus, C5aR expression in UCC may correlate with the low survival rate exhibited by patients (Table II). It has been reported that high C5aR mRNA expression in cancer cells is associated with short survival time in patients with ovarian or lung cancer (24), in accordance with the results of the present study, which revealed that C5aR protein expression of UCC cells correlated with low survival rates in UCC patients ( Fig. 2; Table II).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, C5aR expression in UCC may correlate with the low survival rate exhibited by patients (Table II). It has been reported that high C5aR mRNA expression in cancer cells is associated with short survival time in patients with ovarian or lung cancer (24), in accordance with the results of the present study, which revealed that C5aR protein expression of UCC cells correlated with low survival rates in UCC patients ( Fig. 2; Table II).…”
Section: Discussionsupporting
confidence: 82%
“…Although it has not yet been demonstrated in human UCC, C5aR signaling suppresses apoptosis, induces T-cell expansion via the enhanced expression of Bcl-2 (32) and enhances neuronal cell survival via inhibition of caspase-3 activation (33). C5a is present in the cancer microenvironment (17,20,23), where, by stimulation with C5a, the apoptosis of C5aR-expressing UCC may be suppressed; this supression facilitates the growth and development of cancer in concert with the C5a-elicited enhancement of proliferation (24) and invasiveness (22). Thus, C5aR expression in UCC may correlate with the low survival rate exhibited by patients (Table II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we confirmed CD8 + T cell localization using anti-CD8 antibody and tumor cell apoptosis using terminal deoxynucleotidyl transferase dUTP nick-end labeling assays in the tumor tissue by immunohistochemical staining analysis, as described previously using formalin-fixed, paraffin-embedded EG.7 and TC-1 tumor tissue specimens. 29 The analysis was recorded in five random fields for each slide and was performed by two investigators in a blinded fashion.…”
Section: Antitumor Efficacy Of Dcs Treated With Plga-npsmentioning
confidence: 99%
“…En fonction du type de cancer considéré, l'impact du système du complément peut en effet varier en ce qui concerne les protéines impliquées, mais également en termes de valeur pronostique. Dans la majorité des cancers, comme le cancer du rein [14], du sein [12], du poumon [11], de l'ovaire [18] et urothéliales [15], les protéines du complément favorisent la croissance tumorale. Dans d'autres, comme le cancer de la prostate [19], ces protéines n'ont aucune influence sur la croissance tumorale, elles peuvent même la ralentir.…”
Section: Protéines Du Complément Et Contexte Tumoralunclassified